Analytical and numerical modeling of RC beam-column joints retrofitted with FRP laminates and hybrid composite connectors. (15th April 2019) - Mosallam, Ayman; Allam, Khaled; Salama, Mohamed
Abstract: This paper summarizes results on an analytical and numerical simulation of structural behavior of reinforced concrete (RC) beam-column joints retrofitted with different types of fiber-reinforced-polymeric (FRP) composite laminates and hybrid connectors. In this study, non-linear numerical simulations for the behavior of reinforced concrete (RC) beam-column joints that were evaluated in another phase of this study. The behavior of a total of eight full-scale interior RC beam-column specimens were numerically evaluated. The interior reinforced concrete (RC) beam-column joint specimens were subjected to both simulated gravity and low-frequency full-cyclic reversal loads. For repair and external strengthening applications, three systems are evaluated including high-strength carbon/epoxy composite laminates, high-modulus carbon/epoxy laminates and E-glass/epoxy external laminates. For bond-slip retrofit, the light-weight hybrid composite connector, developed by the principal author, was evaluated through large-scale tests and is molded numerically. Good correlation between numerical and experimental results is achieved. A comparison between the numerical and experimental results are also presented.